COMUNICACIÓN ORAL Y M-LEARNING EN EL AULA DE INGLÉS DE PRIMARIA: LA FOTOGRAFÍA Y EL VÍDEO COMO RECURSO - Marta GARCÍA-SAMPEDRO,Mirian MIRANDA MORAIS,Eva M.ª IÑESTA MENA (Fonseca, Journal of Communication, 2023)
The process of design, implementation and evaluation of the project ‘Films & Photographs: An M-learning Experience in Primary Education’ is presented in this article through the research-action methodology. The project’s main objective was to foster oral communication in the English language (as an additional language) using mobile devices in primary education through photography and video. Two English primary language teachers, two university lecturers and an in-service teacher advisor from the Teachers’ Training and Resource Centre participated in the project